Corporate carbon accounting: balance sheets and flow statements - Stefan Reichelstein (Review of Accounting Studies, 2024)
Abstract Current corporate disclosures regarding carbon emissions lack generally accepted accounting rules. The transactional carbon accounting system described here takes the rules of historical cost accounting for operating assets as a template for generating carbon emissions (CE) statements comprising a balance sheet and a flow statement. The asset side of the CE balance sheet reports the carbon emissions embodied in operating assets. The liability side conveys the firm's cumulative direct emissions into the atmosphere as well as the cumulative emissions embodied in goods acquired from suppliers less those sold to customers. Flow statements report the company's annual corporate carbon footprint calculated as the cradle-to-gate carbon footprint of goods sold during the current period. Taken together, balance sheets and flow statements generate key performance indicators of a company's past, current, and future performance in the domain of carbon emissions.
Additional information: M41;M48;Q53;Q54
Keywords: 330; Net-zero pledges; Carbon emissions; Carbon~accounting; Carbon reporting